A kind of blister coated white paper and preparation process
By guiding the ink penetration in the coating and using aqueous blister oil, combined with the heat sealing temperature and pressure, the modified starch particles are displaced and rearranged with light calcium carbonate, which solves the problem of insufficient binding force between the coating and the white paperboard, and achieves high-quality blister coated white paperboard.
Patent Information
- Application Number
- CN202310811132.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-07-04
AI Technical Summary
Among the existing blister coated white paperboards, the binding force between the coating and the white paperboard is insufficient, especially the weak binding force between the plastic blister and the coating, resulting in unstable quality of the blister gray-bottomed white paperboard.
By guiding the ink penetration in the coating and using aqueous blister oil, combined with the heat sealing temperature and pressure, the modified starch particles are displaced and rearranged with the light calcium carbonate to form a tight connection between the aqueous blister oil and the gray-bottomed white cardboard.
The adhesive uniformity and bonding force between the plastic blister and the gray-bottomed white cardboard is significantly improved, ensuring the quality reliability of the blister coated white cardboard.
Smart Images

Figure CN116905276B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gray-bottom white paperboard, in particular to a blister-coated white paperboard and a preparation process thereof. Background Art
[0002] Blister packaging is to use blister oil to penetrate into the paper layer of gray-bottomed white paperboard after printing a pattern on the coating surface of the coated white paperboard, so that the bonding strength between the coating of the gray-bottomed white paperboard and the paper is greater than the strength inside the paper layer. The invention patent CN103993500B discloses a blister-specific coated white paperboard and its preparation process, which improves the weak bonding between the coating and the white paperboard and enhances the bonding between the coating and the base paper; however, if the coating is closed, the bonding between the plastic blister and the coating is weak and it is difficult to obtain a reliable quality blister gray-bottomed white paperboard. Summary of the invention
[0003] The purpose of the present invention is to provide a preparation process of blister coated white paper. The present invention utilizes relatively large pores connected to the coating generated during the drying process of the coating to guide the penetration of ink and the coating of water-based blister oil. With the temperature and pressure of heat sealing, the modified starch particles in the coating are displaced and rearranged with light calcium carbonate, forming a close connection and contact between the water-based blister oil and the gray-bottomed white paperboard.
[0004] To solve this technical problem, the technical solution of the present invention is: a preparation process of blister coated white paper, comprising the following steps:
[0005] Step 1: coating a first coating layer, a second coating layer and a third coating layer in sequence from bottom to top on a surface layer of a white paperboard to form a coating, wherein the pigment in the first coating layer comprises heavy calcium carbonate and kaolin, the pigment in the second coating layer comprises heavy calcium carbonate, and the pigment in the third coating layer is light calcium carbonate particles;
[0006] The adhesive in the coating is carboxylated styrene butadiene latex and modified starch, wherein the modified starch is enzymatically hydrolyzed and oxidized starch cross-linked N-hydroxymethyl acrylamide;
[0007] Step 2: drying, the modified starch forms particles due to the presence of N-hydroxymethyl acrylamide, and a pore structure penetrating the coating is formed on the coating surface;
[0008] Step 3: printing ink on the surface of the gray-bottomed white paperboard obtained in step 2, and the ink penetrates into the white paperboard through the pore structure of the coating;
[0009] Inject IGT standard offset ink into IGT high-speed ink distribution device through ink injector, inject ink on ink distribution roller, squeeze the coating during printing, and the printing pressure is 580N to 600N;
[0010] Step 4: Apply a single layer of water-based blister oil and dry with hot air;
[0011] Step 5: The water-based blister oil is heated to a melting temperature, the plastic blister is bonded to the white paper including the coating, and heat-sealed, and the modified starch particles in the coating are deformed around the connecting channels and closely contact the water-based blister oil to obtain a blister-coated white paperboard.
[0012] Preferably, the particle morphology specifications of the heavy calcium carbonate and kaolin in the first coating layer are as follows: the number ratio of the heavy calcium carbonate particles with a diameter less than 2 μm is 75% to 85%; the number ratio of the kaolin particles with a diameter less than 2 μm is greater than 80%; the total mass of the heavy calcium carbonate and kaolin is calculated as one hundred parts, wherein the mass ratio of the heavy calcium carbonate to the kaolin is (65 to 70): (30 to 35);
[0013] The second pigment comprises heavy calcium carbonate, wherein the number ratio of the heavy calcium carbonate particles having a diameter less than 2 μm is 60% to 75%;
[0014] The third pigment includes light calcium carbonate nanoparticles, wherein the D90 of the light calcium carbonate is 100nm to 200nm;
[0015] The adhesive comprises modified starch and carboxylated styrene-butadiene latex in a mass ratio of (1 to 1.2):1.
[0016] The hydroxyl groups on the starch molecular chain segments are hydrophilic groups and cannot form a network cross-linked structure when solidified. In the process of mixing with styrene-butadiene latex, the cross-linked structure formed by the starch molecular chain segments has low strength, making it difficult to increase the amount of starch in the modified starch-carboxyl styrene-butadiene latex. In order to overcome the problems existing in the above-mentioned prior art, the present invention utilizes the coordination of pigment particles in the multi-layer structure of the coating to reduce the penetration of moisture in the coating into the surface layer, promotes the volatilization of moisture, and thus forms continuous channels in the coating; at the same time, N-hydroxymethyl acrylamide in the modified starch is cross-linked with short-chain starch and itself to form more covalent bonds. With the help of the pressure and temperature of heat sealing, the small starch particles formed by cross-linking with N-hydroxymethyl acrylamide are squeezed and deformed during the heat sealing process. During the deformation process, on the one hand, they come into contact with other particles; on the other hand, the continuous channels originally formed by the evaporation of water are displaced due to extrusion to form a continuous pore size, thereby forming a tight connection with the water-based blister oil;
[0017] The present invention uses both irregularly shaped heavy calcium carbonate and flaky kaolin in the first coating layer. The heavy calcium carbonate has irregular particles due to mechanical crushing and classification, and the particles are relatively large in size. The combination with the flaky kaolin limits the downward migration of the coating to a certain extent. The pigment in the second coating layer is heavy calcium carbonate, and the pigment in the third coating layer is light calcium carbonate. During the drying process, the water in the coating first evaporates to form a connecting channel from bottom to top. Since the first coating layer and the second coating layer both use heavy calcium carbonate and flaky kaolin with relatively large particles, the specific surface area of the coating is relatively large. The light calcium carbonate with a small surface area and a small particle size in the third coating layer and a large specific surface area, that is, the dispersion of water in the first coating layer and the second coating layer is more concentrated than that in the third coating layer. During the drying process, the water volatilizes more concentratedly from the third coating layer, the second coating layer to the third coating layer to form a larger interconnected pore, and the modified starch particles are also distributed on both sides of the pore; compared with starch that has not been enzymatically hydrolyzed and oxidized, the modified starch used in the present invention has a short-chain structure, and there is a certain gap inside after being balled, and the short-chain starch is different from the long-chain starch in a spiral structure in water. The modified starch particles are hard to deform due to their structure. During the printing and heating and heat sealing process of the modified starch particles, the pigment particles are rearranged to a certain extent under the action of pressure. The modified starch particles still maintain the limitation and adhesion to the hard calcium carbonate, kaolin and light calcium carbonate during extrusion. The deformation of the modified starch particles under pressure has a smaller distance between the adhesive molecules, which promotes the formation of hydrogen bonds between the adhesive and the surface molecules of the object to be bonded, and the adhesion is firm. On the other hand, the deformation of the modified starch particles themselves cooperates with the pressure to make their shapes more irregular and fill them between the pigment particles, reducing the adhesive. The adhesive migrates, and the obtained coating structure is stable; the light calcium carbonate and modified starch particles in the third coating layer of the present invention undergo a certain degree of structural collapse surrounding the aqueous blister oil in the connecting channels, the first coating layer, the second coating layer and the third coating layer The large particles of heavy calcium carbonate and kaolin from bottom to top are matched with the particle gaps and the connecting channels in the third coating layer are relatively concentrated in the thickness direction due to the evaporation of water vapor, and the aqueous blister oil penetrates into the fibers of the white paperboard with a root structure, thereby effectively improving the uniformity of the adhesion between the plastic blister of the obtained blister-coated white paperboard and the gray-bottomed white paperboard.
[0018] The substance for modifying starch in the present invention is N-hydroxymethyl acrylamide, starch is abbreviated as St, and the cross-linking reaction formula with N-hydroxymethyl acrylamide is as follows:
[0019]
[0020] N-hydroxymethyl acrylamide has good water solubility and contains carbon-carbon double bonds, which can easily react with short-chain starch molecules. The N-hydroxymethyl acrylamide grafted on the surface of short-chain starch molecules effectively promotes the spatial network connection between starches. Stronger chemical bonds are formed between modified starches, and the binding force between starch molecules is increased. Combined with heat sealing at high temperature, the structural strength of the coating is guaranteed.
[0021] The process of forming the pigment particles in the coating layer in close contact with the water-based blister oil by heat sealing is preferably as follows:
[0022] During the drying process, the modified starch in the coating aggregates into small particles, and at the same time, the evaporation of water in the coating forms interconnected channels from bottom to top;
[0023] During the bonding process of step five, the modified starch particles in the coating layer are squeezed, deformed, and filled between the pigments; wherein the modified starch particles in the third coating layer move synchronously with the light calcium carbonate nanoparticles to form a tight structure surrounding the aqueous blister oil.
[0024] Preferably, the modification method of the modified starch comprises the following steps:
[0025] S1, enzymatic hydrolysis of long-chain starch into short-chain starch;
[0026] Add starch, α-amylase and water into a three-necked flask equipped with a reflux condenser, a stirrer and a constant pressure dropping funnel, and react in a water bath at 40°C to 60°C for 30min to 60min;
[0027] S2, secondary shortened short-chain starch;
[0028] Disperse the short-chain starch obtained in step 1 in deionized water, with the ratio of short-chain starch to deionized water being 0.5 g:2 ml;
[0029] Heat in a water bath at 30 to 40° C., adjust the pH value of the short-chain starch-deionized water dispersion system to 9 to 10 with sodium hydroxide, add hydrogen peroxide, stir, and react for 30 to 60 min, the volume ratio of hydrogen peroxide to deionized water is (0.5% to 0.8%): 1; the oxidation process shortens the starch chain again;
[0030] S3, using hydrochloric acid to adjust the pH value of the reaction system after step 2 to 4 to 5; using deionized water to dissolve N-hydroxymethyl acrylamide and add it to the reaction system of step 2;
[0031] Raise the temperature to 80° C. to 85° C., add initiator ammonium persulfate, and keep warm for 30 min to 50 min to obtain N-hydroxymethyl acrylamide-modified short-chain starch; the mass of the initiator is 0.08% to 0.12% of the mass of the starch in step 1;
[0032] The mass of N-hydroxymethyl acrylamide is 10% to 12% of the mass of starch in S1.
[0033] The present invention uses α-amylase to hydrolyze α-1,4-glucosidic bonds in starch molecular chains, cuts the starch chains, and reduces starch viscosity.
[0034] In the present invention, enzymolysis is used to shorten the chain length of starch molecules for the first time, so that macromolecules are degraded, the steric hindrance of starch is reduced, the fluidity of the coating is improved, and the shortened starch chains expose more hydroxyls, which is also convenient for further modification of short-chain oxidized starch; the present invention exposes more hydroxyls through double shortening treatment of enzymolysis and oxidation, and uses cross-linking grafting modification of N-hydroxymethyl acrylamide to cooperate with the evaporation of water during the drying process. While forming a connecting channel from bottom to top, the short-chain starch forms small particles due to the cross-linking of N-hydroxymethyl acrylamide. Further cooperate with the heat sealing of the bonding process, the change of the distance between the substances, the small particles of modified starch are deformed by extrusion, and the distribution of light calcium carbonate particles, heavy calcium carbonate particles and kaolin is coordinated. The modified starch particles are deformed and closely structured with the water-based blister oil dispersed in the root structure, and the multi-layer structure of the coating is also more closely connected.
[0035] Preferably, the adhesive used in the first coating layer is the first adhesive, the adhesive used in the second coating layer is the second adhesive, and the adhesive used in the third coating layer is the third adhesive, wherein the mass ratio of the carboxylated styrene butadiene latex to the first pigment or the second pigment or the third pigment is 10% to 12%;
[0036] The mass ratios of modified starch to carboxylated styrene butadiene latex in the first adhesive, the second adhesive and the third adhesive are M1, M2 and M3 respectively, wherein M1<M2<M3. The present invention uses the amount of modified starch to control the amount of modified starch particles formed, promoting the formation of root structure channels that are concentrated at the top and dispersed at the bottom.
[0037] It is preferred to use an automatic coating machine to evenly coat the coating on the surface layer, and the coating amount of each layer is controlled at 3g / m 2 Up to 4g / m 2 .
[0038] The preferred baking process conditions are as follows:
[0039] The drying temperature is increased to 120° C. for 1 to 2 minutes. The present invention increases the drying temperature and shortens the drying time, so that the water in the water layer is quickly and concentratedly separated, thereby promoting the formation of root pores.
[0040] The process conditions for drying in step 4 are preferably as follows:
[0041] The drying temperature is 75°C and the drying belt movement speed is 2.5 cm / s;
[0042] The process parameters of heat sealing in step 5 are preferably as follows: heat sealing time 1s, heat sealing upper temperature 150°C, heat sealing lower temperature 120°C, and heat sealing pressure 1.0Mpa. In the present invention, the heat sealing pressure is increased, which effectively promotes the modified starch particles in the coating to adapt to the melting deformation of the water-washed blister oil during the bonding process, and the contact between the plastic blister and the gray-bottomed white paperboard is close and uniform.
[0043] Preferably, the solid content of the coating is 58% to 63%. The present invention effectively ensures the amount of water used and the formation of connecting channels.
[0044] By adopting the above technical solution, the beneficial effects of the present invention are:
[0045] The present invention uses modified starch with N-hydroxymethyl acrylamide distributed from bottom to top in the coating of gray-bottom white paperboard as the first coating layer, the second coating layer and the third coating layer of the adhesive to form a coating, wherein the pigment in the first coating layer includes heavy calcium carbonate and kaolin, the pigment in the second coating layer includes heavy calcium carbonate, and the pigment in the third coating layer is light calcium carbonate particles; along with the drying in step 2, the modified starch forms particles due to the presence of N-hydroxymethyl acrylamide, and a pore structure penetrating the coating is formed on the surface of the coating;
[0046] Based on the existence of the pores in step 2, the ink in the printing process penetrates into the white paperboard through the pore structure of the coating; the transfer of the ink can reach the white paperboard part faster; then, with the existence of the pore structure of the coating, the applied water-based blister oil penetrates into the coating along the through holes and contacts the fiber part of the white paperboard; the present invention utilizes the pores of water evaporation to form ink and water-based blister oil to be introduced into the coating and further into the white paperboard, thereby promoting the uniform distribution of the water-based blister oil, and along the thickness direction of the gray-bottom white paper, the water vapor evaporation is utilized to form the ink and water-based blister oil to be introduced into the coating and further into the white paperboard. The formed continuous channels are used to guide the penetration and dispersion of the water-based blister oil, and further cooperate with the irregular heavy calcium carbonate particles and kaolin dispersion in the coating to disperse the originally concentrated water-based blister oil into the white board paper, thereby forming a continuous and uniform distribution of the water-based blister oil; the water-based blister oil is heated to melt, the plastic blister and the white board paper are bonded and heat-sealed through the water-based blister oil, and the modified starch particles in the coating tightly fit and deform around the connecting channels and the water-based blister oil in the channels, and the plastic blister and the coated white board have uniform and good bonding force. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 is an infrared spectrum of the modified starch prepared in Example 1 of the present invention;
[0048] Figure 2 This is a schematic diagram of the structure of the gray-bottomed white paperboard coating that has not been dried in the present invention;
[0049] Figure 3This is a schematic diagram of the structure of the gray-bottomed white paperboard coating after drying in the present invention;
[0050] Figure 4 It is a schematic diagram of the penetration distribution process of coating the grey-bottomed white paperboard with water-based blister oil in the present invention.
[0051] In the figure:
[0052] White paperboard 100; coating 200; first coating layer 210; second coating layer 220; third coating layer 230; connecting channel 300; particles 400; water-based blister oil 500. DETAILED DESCRIPTION
[0053] In order to further explain the technical solution of the present invention, the present invention is described in detail below through specific embodiments.
[0054] The invention uses a first coating layer, a second coating layer and a third coating layer of modified starch with N-hydroxymethyl acrylamide distributed from bottom to top in a coating of a gray-bottomed white paperboard as an adhesive, wherein the pigment in the first coating layer includes heavy calcium carbonate and kaolin, the pigment in the second coating layer includes heavy calcium carbonate, and the pigment in the third coating layer is light calcium carbonate particles; along with the drying in step 2, the modified starch forms particles due to the presence of N-hydroxymethyl acrylamide, and a pore structure penetrating the coating is formed on the surface of the coating; based on the presence of the pores in step 2, the ink in the printing process penetrates into the white paperboard through the pore structure of the coating; the transfer of the ink can quickly reach the white paperboard part; subsequently, with the presence of the pore structure of the coating, the applied water-based blister oil penetrates into the coating along the through holes and is bonded to the white paperboard. The fiber part of the paperboard is in contact with the ink; the present invention utilizes the pores formed by water evaporation to introduce ink and water-based blister oil into the coating and further into the white paperboard, thereby promoting the uniform distribution of the water-based blister oil, and along the thickness direction of the gray-bottom white paperboard, the continuous pores formed by water vapor evaporation are used to guide the penetration and dispersion of the water-based blister oil, and further cooperate with the irregular heavy calcium carbonate particles and kaolin dispersion in the coating to disperse the originally concentrated water-based blister oil into the white paperboard, thereby forming a continuous and uniform distribution of the water-based blister oil; the water-based blister oil is heated to melt, the plastic blister is bonded to the white paperboard through the water-based blister oil, and heat-sealed, the modified starch particles in the coating are tightly deformed around the connecting pores and the water-based blister oil in the pores, and the plastic blister has a uniform and good bonding force with the coated white paperboard.
[0055] Example 1
[0056] This embodiment discloses a method for modifying modified starch coated with a gray-bottom white paperboard coating layer as an adhesive, comprising the following steps:
[0057] S1, enzymatic hydrolysis of long-chain starch into short-chain starch;
[0058] Add starch, α-amylase and water into a three-necked flask equipped with a reflux condenser, a stirrer and a constant pressure dropping funnel, and react in a water bath at 60°C for 60 min; the mass ratio of α-amylase to starch is 1 mg:5 g;
[0059] S2, secondary shortened short-chain starch;
[0060] Disperse the short-chain starch obtained in step 1 in deionized water, with the ratio of short-chain starch to deionized water being 0.5 g:2 ml;
[0061] Heat in a water bath at 40°C, adjust the pH value of the short-chain starch-deionized water dispersion system to 9 with sodium hydroxide, add hydrogen peroxide, stir, and react for 60 min, the volume ratio of hydrogen peroxide to deionized water is 0.5%:1; the hydroxyl groups of the short-chain starch are oxidized to aldehyde groups or carboxyl groups;
[0062] S3, using hydrochloric acid to adjust the pH value of the reaction system after step 2 to 5; using deionized water to dissolve N-hydroxymethyl acrylamide and add it to the reaction system of step 2;
[0063] The temperature was raised to 85° C., and ammonium persulfate as an initiator was added, and the temperature was kept for 50 min to obtain short-chain starch modified with N-hydroxymethyl acrylamide; the mass of the initiator was 0.08% of the mass of the starch in step one.
[0064] In this embodiment, the mass of N-hydroxymethyl acrylamide is 10% of the mass of starch in S1.
[0065] The infrared spectrum of the modified starch obtained in this example is as follows Figure 1 As shown. Figure 1 It can be seen that the infrared spectrum of the modified starch obtained in this example is at 3338cm -1 The stretching vibration absorption peak of starch-OH appeared at 2926cm -1 The stretching vibration absorption peak of starch-CH2 appeared at 1035cm -1 The stretching vibration absorption peak of starch CO appeared at Figure 1 There are also characteristic peaks of N-hydroxymethyl acrylamide, such as at 1660cm -1 The C=O vibration peak of secondary amide appeared at 1552 cm -1 The bending vibration peak of the secondary amide N—H appeared at , indicating that the present embodiment effectively grafted N-hydroxymethyl acrylamide onto the short-chain starch.
[0066] Example 2
[0067] This embodiment discloses a preparation process of blister coated white paper, comprising the following steps:
[0068] Step 1: Figure 2As shown, a first coating layer 210, a second coating layer 220 and a third coating layer 230 are sequentially coated on the surface layer of a white paperboard 100 from bottom to top to form a coating layer 200, wherein the coating layer 200 uses modified starch and carboxylated styrene butadiene latex as adhesives, wherein the mass ratio of carboxylated styrene butadiene latex to the first pigment or the second pigment or the third pigment is 12%;
[0069] The mass ratios of the modified starch to the carboxylated styrene butadiene latex in the first adhesive, the second adhesive and the third adhesive are M1, M2 and M3 respectively. In this embodiment, M1 is 1.0, M2 is 1.1 and M3 is 1.2.
[0070] The first coating layer comprises the following substances in parts by mass:
[0071]
[0072]
[0073] The first pigment includes heavy calcium carbonate and kaolin, wherein the weight ratio of the heavy calcium carbonate particles smaller than 2 μm is 75%; the weight ratio of the kaolin particles smaller than 2 μm is 85%; the total weight of the heavy calcium carbonate and the kaolin is calculated as 100 parts, wherein the weight ratio of the heavy calcium carbonate to the kaolin is 65 parts:35 parts;
[0074] The composition of the second coating layer includes the following substances in parts by mass:
[0075]
[0076] The second pigment comprises heavy calcium carbonate, wherein the number ratio of the heavy calcium carbonate particles having a diameter less than 2 μm is 60%;
[0077] The composition of the third coating layer includes the following substances in parts by mass:
[0078]
[0079]
[0080] The third pigment includes light calcium carbonate, wherein the D90 of the light calcium carbonate is 100 nm;
[0081] Water was added separately and stirred, and the solid content of the obtained coating was 58%.
[0082] Use an automatic coating machine to evenly apply the coating on the surface layer, and the coating amount of each layer is controlled at 3g / m 2 Up to 4g / m 2 .
[0083] Step 2: Drying: the modified starch forms particles 300 due to the presence of N-hydroxymethyl acrylamide, and a pore structure 400 that penetrates the coating is formed on the coating surface, such as Figure 3 As shown;
[0084] The baking process conditions are as follows:
[0085] Dry at 120℃ for 1min.
[0086] Step 3: printing ink on the surface of the gray-bottomed white paperboard obtained in step 2, and the ink penetrates into the white paperboard through the pore structure of the coating;
[0087] Inject IGT standard offset ink into IGT high-speed ink distribution device through ink injector, inject ink on ink distribution roller, squeeze the coating during printing, and the printing pressure is 580N to 600N;
[0088] Step 4: Apply a single layer of water-based blister oil 500, such as Figure 4 As shown, water-based blister oil 500 is Figure 3 The formed channels in the coating 200 and the white paperboard 100 are reversely entered and dried with hot air;
[0089] The drying process conditions are as follows:
[0090] The drying temperature is 75°C and the drying belt movement speed is 2.5 cm / s;
[0091] Step 5: The water-based blister oil is heated to a melting temperature, and the plastic blister is bonded to the white paper including the coating, bonded and extruded, and the modified starch particles in the coating are deformed around the connecting channels and closely contact the water-based blister oil to obtain a blister-coated white paperboard;
[0092] The process parameters of heat sealing in step 5 are as follows: heat sealing time 1 s, heat sealing temperature 120° C., and heat sealing pressure 1.0 MPa.
[0093] The process of forming the pigment particles in the coating and forming a close contact with the water-based blister oil as the heat seal is squeezed is as follows:
[0094] During the drying process, the modified starch in the coating aggregates into small particles, and at the same time, the evaporation of water in the coating forms interconnected channels from bottom to top;
[0095] During the bonding process of step five, the modified starch particles in the coating are squeezed and deformed and filled between the pigments; the modified starch particles in the third coating layer move synchronously with the light calcium carbonate nanoparticles to form a tight structure around the aqueous blister oil, and deform synchronously with the melting of the aqueous blister oil.
[0096] Example 3
[0097] The main difference between this embodiment and embodiment 2 is that:
[0098] The first pigment includes heavy calcium carbonate and kaolin, wherein the number ratio of heavy calcium carbonate particles with a diameter less than 2 μm is 80%; the number ratio of kaolin particles with a diameter less than 2 μm is 85%; the total mass of heavy calcium carbonate and kaolin is calculated as one hundred parts, wherein the mass ratio of heavy calcium carbonate to kaolin is 70 parts:30 parts.
[0099] The second pigment includes heavy calcium carbonate, wherein the number ratio of the heavy calcium carbonate particles having a diameter less than 2 μm is 70%.
[0100] The drying process conditions in step 2 are drying at 110° C. for 2 min.
[0101] The printing pressure in step three is 600N.
[0102] Example 4
[0103] The main difference between this embodiment and embodiment 2 is that:
[0104] The first pigment includes heavy calcium carbonate and kaolin, wherein the number ratio of heavy calcium carbonate particles with a diameter less than 2 μm is 85%; the number ratio of kaolin particles with a diameter less than 2 μm is 85%; the total mass of heavy calcium carbonate and kaolin is calculated as one hundred parts, wherein the mass ratio of heavy calcium carbonate to kaolin is 70 parts:30 parts.
[0105] The second pigment includes heavy calcium carbonate, wherein the number ratio of the heavy calcium carbonate particles having a diameter less than 2 μm is 75%.
[0106] The drying process conditions in step 2 are drying at 110° C. for 2 min.
[0107] The printing pressure in step three is 580N.
[0108] Comparative Example
[0109] The main difference between this comparative example and Example 2 is that the unmodified starch used in the comparative example replaces the modified starch in the adhesive. The process conditions of drying and heat sealing are the same as those in Example 2.
[0110] The surface roughness of the coated gray-bottomed white paperboard obtained in Examples 2, 3 and 4 and the comparative example after drying in step 2, the penetration depth of the aqueous blister oil and the peel strength of the PVC plastic blister are shown in Table 1. The gray-bottomed white paperboard with a length of 60 mm and a width of 15 mm and the PVC plastic blister are heat-sealed with a heat-sealed length of 10 mm. After cooling for 24 hours, the tensile speed is set to 300 mm / min on the electronic tensile testing machine to measure the peel strength.
[0111] Table 1 Blister properties of coated white paperboards obtained in Examples 2 to 4 and Comparative Examples
[0112] project Roughness after drying Coating thickness Penetration Depth Peel strength Example 2 1.39μm 7.9μm 15.7μm 1.71N Example 3 1.38μm 7.6μm 15.2μm 1.66N Example 4 1.39μm 7.8μm 15.4μm 1.69N Comparative Example 1.46μm 7.8μm 8.6μm 1.13N
[0113] Combined with Table 1, it can be seen that compared with the comparative example using unmodified starch and carboxylated styrene butadiene latex as adhesives, the unmodified starch particles are large in size and difficult to form particles. The present invention uses the modified starch with N-hydroxymethyl acrylamide distributed from bottom to top in the coating of the gray-bottomed white paperboard as the first coating layer, the second coating layer and the third coating layer of the adhesive to form a coating, wherein the pigment in the first coating layer includes heavy calcium carbonate and kaolin, the pigment in the second coating layer includes heavy calcium carbonate, and the pigment in the third coating layer is light calcium carbonate particles; accompanied by the drying of step 2, the modified starch forms particles due to the presence of N-hydroxymethyl acrylamide, and a pore structure penetrating the coating is formed on the surface of the coating; and after the drying of step 2, the modified starch forms particles due to the cross-linking modification of N-hydroxymethyl acrylamide, and accompanied by the escape of water, the light calcium carbonate particles around the connected pores in the third coating layer and the modified starch particles are densified compared to the drying, and the heavy calcium carbonate and kaolin particles in the first coating layer and the second coating layer are larger, because the displacement formed by the detachment of water is less, thereby forming a pore structure in the third coating layer. The coating is concentrated and the connected channels with root structure are dispersed in the second coating layer and the first coating layer; then, with the existence of the coating channel structure, the applied water-based blister oil penetrates into the coating along the through holes and contacts with the fiber part of the white paperboard; the present invention utilizes the channels formed by water evaporation to introduce ink and water-based blister oil into the coating and further into the white paperboard, thereby promoting the uniform distribution of the water-based blister oil, and along the thickness direction of the gray-bottom white paperboard, the continuous channels formed by water vapor evaporation are used to guide the penetration and dispersion of the water-based blister oil, and further With the irregular heavy calcium carbonate particles and kaolin dispersion in the coating, the originally concentrated water-based blister oil is dispersed into the white paper, thereby forming a continuous and uniform distribution of the water-based blister oil. Therefore, the water-based blister oil can effectively penetrate with a root structure and the penetration depth is sufficient; the water-based blister oil is heated to melt, and the plastic blister is bonded and squeezed with the white paper through the water-based blister oil. At the same time, the modified starch particles in the coating are closely attached to and deformed synchronously around the connecting channels and the molten water-based blister oil in the channels, and the plastic blister and the coated white paperboard have uniform and good bonding force.
Claims
1. A process for preparing blister coated white paper, characterized in that: The following steps are involved: Step 1: coating a first coating layer, a second coating layer and a third coating layer in sequence from bottom to top on a surface layer of a white paperboard to form a coating, wherein the pigment in the first coating layer comprises heavy calcium carbonate and kaolin, the pigment in the second coating layer comprises heavy calcium carbonate, and the pigment in the third coating layer is light calcium carbonate particles; The adhesive in the coating is carboxylated styrene butadiene latex and modified starch, wherein the modified starch is enzymatically hydrolyzed and oxidized starch cross-linked N-hydroxymethyl acrylamide; Step 2: drying, the modified starch forms particles due to the presence of N-hydroxymethyl acrylamide, and a pore structure penetrating the coating is formed on the coating surface; Step 3: printing ink on the surface of the gray-bottomed white paperboard obtained in step 2, and the ink penetrates into the white paperboard through the pore structure of the coating; Inject IGT standard offset ink into IGT high-speed ink distribution device through ink injector, inject ink on ink distribution roller, squeeze the coating during printing, and the printing pressure is 580N to 600N; Step 4: Apply a single layer of water-based blister oil and dry with hot air; Step 5: The water-based blister oil is heated to a melting temperature, the plastic blister is bonded to the white paper including the coating, and heat-sealed, and the modified starch particles in the coating are deformed around the connecting pores and closely contact the water-based blister oil to obtain a blister-coated white paperboard; The modification method of the modified starch comprises the following steps: S1, enzymatic hydrolysis of long-chain starch into short-chain starch; Add starch, α-amylase and water to a three-necked flask equipped with a reflux condenser, a stirrer and a constant pressure dropping funnel, and react in a water bath at 40°C to 60°C for 30min to 60min; S2, secondary shortened short-chain starch; Disperse the short-chain starch obtained in step 1 in deionized water, with the liquid ratio of short-chain starch to deionized water being 0.5 g:2 ml; Heat in a water bath at 30 to 40°C, adjust the pH value of the short-chain starch-deionized water dispersion system to 9 to 10 with sodium hydroxide, add hydrogen peroxide, stir, and react for 30 to 60 minutes, the volume ratio of hydrogen peroxide to deionized water is (0.5% to 0.8%): 1; S3, using hydrochloric acid to adjust the pH value of the reaction system after step 2 to 4 to 5; using deionized water to dissolve N-hydroxymethyl acrylamide and add it to the reaction system of step 2; Raise the temperature to 80°C to 85°C, add initiator ammonium persulfate, and keep warm for 30 to 50 minutes to obtain short-chain starch modified with N-hydroxymethyl acrylamide; the mass of the initiator is 0.08% to 0.12% of the mass of the starch in step 1; The mass of N-hydroxymethyl acrylamide is 10% to 12% of the mass of starch in S1.
2. The process for preparing a blister coated whiteboard paper according to claim 1, characterized in that: The particle morphology specifications of the heavy calcium carbonate and kaolin in the first coating layer are as follows: the number ratio of the heavy calcium carbonate particles with a diameter less than 2 μm is 75% to 85%; the number ratio of the kaolin particles with a diameter less than 2 μm is greater than 80%; the total mass of the heavy calcium carbonate and kaolin is calculated as one hundred parts, wherein the mass ratio of the heavy calcium carbonate and kaolin is (65 to 70): (30 to 35); The pigment in the second coating layer includes heavy calcium carbonate, wherein the number ratio of the heavy calcium carbonate particles having a diameter less than 2 μm is 60% to 75%; The pigment of the third coating layer includes light calcium carbonate nanoparticles, wherein the D90 of the light calcium carbonate is 100nm to 200nm; The adhesive includes modified starch and carboxylated styrene butadiene latex in a mass ratio of (1 to 1.2):
1.
3. The process for preparing a blister coated whiteboard paper according to claim 2, characterized in that: The process of forming the modified starch particles in the coating and forming a close contact with the water-based blister oil as the heat seal is as follows: During the drying process, the modified starch in the coating aggregates into small particles, and at the same time, the evaporation of water in the coating forms interconnected channels from bottom to top; During the bonding process of step five, the modified starch particles in the coating layer are squeezed, deformed, and filled between the pigments; wherein the modified starch particles in the third coating layer move synchronously with the light calcium carbonate nanoparticles to form a tight structure surrounding the aqueous blister oil.
4. The process for preparing a blister coated white paperboard according to claim 2, characterized in that: The adhesive used in the first coating layer is the first adhesive, the adhesive used in the second coating layer is the second adhesive, and the adhesive used in the third coating layer is the third adhesive, wherein the mass ratio of carboxylated styrene butadiene latex to the pigment in the first coating layer or the pigment in the second coating layer or the pigment in the third coating layer is 10% to 12%; The mass ratios of modified starch to carboxylated styrene-butadiene latex in the first adhesive, the second adhesive and the third adhesive are M1, M2 and M3 respectively, wherein M1<M2<M3.
5. The process for preparing a blister coated white paperboard according to claim 1, characterized in that: Use an automatic coating machine to evenly apply the coating on the surface layer, and the coating amount of each layer is controlled at 3g / m 2 Up to 4g / m 2 .
6. The process for preparing a blister coated white paperboard according to claim 1, characterized in that: The drying process conditions are as follows: Dry at 110℃ to 120℃ for 1min to 2min.
7. The process for preparing a blister coated white paperboard according to claim 1, characterized in that: The process conditions for drying in step 4 are as follows: The drying temperature was 75°C and the drying belt movement speed was 2.5 cm / s.
8. The process for preparing a blister coated white paperboard according to claim 1, characterized in that: The process parameters of heat sealing in step 5 are as follows: heat sealing time 1 s, heat sealing upper temperature 150° C., heat sealing lower temperature 120° C., and heat sealing pressure 1.0 MPa.
9. A process for preparing a blister coated white paperboard according to any one of claims 1 to 8, characterized in that: The solids content of the coating is 58% to 63%.
Citation Information
Patent Citations
Special Blister Coated White Board Paper and Its Preparation Process
CN103993500B
White board paper used for coating
CN103184710A
Paint special for paperboard coating and paperboard
CN111379192A